An 1-V wide-linear-range weak inversion operational transconductance amplifier for low power applications - Surachoke Thanapitak (2018)
A low voltage, low power and wide linear range operational transconductance amplifier (OTA) which operate in weak inversion is presented. By employing three different transconductor linearisation techniques: bulk driven, floating gate MOSFET and drain current normalisation, this proposed OTA has the linear range of 2.29 Vpp for 1% transconductance gain variation, according to simulating results in a standard 0.18μm CMOS process. The power consumption of this proposed OTA is 48.98nW at 10nA bias current. © 2013 IEEE.